PEDAGOGICAL FOUNDATIONS OF THE COMPETENCY-BASED APPROACH IN BIOLOGY EDUCATION (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the theoretical and methodological foundations of the competency-based approach in biology education. The importance of the competency-based approach in teaching biology, and its role in fostering students' biological literacy, ecological culture, scientific worldview, and practical skills, is highlighted. Additionally, the impact of using modern pedagogical technologies, digital educational tools, and innovative methods in biology education on the development of competencies has been analyzed. Based on the research findings, recommendations have been developed for improving the teaching of biology using a competency-based approach.